The Impact of Maternal Age on Chromosomal Aneuploidy, Blastocyst Quality, and Pregnancy Outcomes During Intracytoplasmic Sperm Injection Cycles - Shahrzad Aghajani; Ali Salehzadeh; Fatemeh Ghasemiyan; Marziyeh Mehrafza; Ahmad Hosseini (Fasa University of Medical Sciences, 2021)
Background & Objective: Assisted reproduction techniques and preimplantation genetic testing (PGT) for aneuploidies help infertile couples achieve a healthy live birth. The objective of this study was to investigate if there is a correlation between chromosomal aneuploidy and maternal age. Materials & Methods: We used 277 embryos with 6-8 cells and graded A derived from intracytoplasmic sperm injection cycles. There were two subgroups: fresh-PGT cycles (n = 38) and Frozen Embryo Transfer (FET) cycles (n = 38). The PGT cycles results were evaluated by fluorescence in situ hybridization and polymerase chain reaction assays. Couples (n = 76) with PGT on the third day were classified into four maternal age groups: ≤35 years (n = 35), 36-40 years (n = 24), 41-45 years (n = 11), and ≥46 years (n = 6). The rate of aneuploidy, blastocyst quality, and pregnancy was assessed in FET and fresh-PGT cycle. Results: Aneuploidy rate in 13, 18, 21, X, and Y chromosomes in FET and fresh-PGT cycles are not significantly related to maternal age (p = 0.1). Significant differences were found in a decreased chemical pregnancy (p = 0.001), clinical pregnancy (p = 0.001), ongoing pregnancy (p = 0.001), and live birth rate (p = 0.001) among both groups. Decreased blastocyst rate increased maternal age in fresh PGT and FET PGT (p = 0.02). Early and clinical pregnancy loss was not related significantly to maternal age. Conclusion: After evaluating cycle characteristics, an association was found between maternal age and declined pregnancy outcomes in embryos. There was a significant relationship between increasing female age with decreasing blastocyst rate.